2016
DOI: 10.1093/nar/gkw213
|View full text |Cite|
|
Sign up to set email alerts
|

The PIN domain endonuclease Utp24 cleaves pre-ribosomal RNA at two coupled sites in yeast and humans

Abstract: During ribosomal RNA (rRNA) maturation, cleavages at defined sites separate the mature rRNAs from spacer regions, but the identities of several enzymes required for 18S rRNA release remain unknown. PilT N-terminus (PIN) domain proteins are frequently endonucleases and the PIN domain protein Utp24 is essential for early cleavages at three pre-rRNA sites in yeast (A0, A1 and A2) and humans (A0, 1 and 2a). In yeast, A1 is cleaved prior to A2 and both cleavages require base-pairing by the U3 snoRNA to the central … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
77
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 61 publications
(81 citation statements)
references
References 37 publications
3
77
0
1
Order By: Relevance
“…This sequence is not known to be the target of any endoribonuclease activity. However, recent RNA–protein crosslinking data (CRAC analysis (39)) showed that the Utp24 endoribonuclease was predominately associated with sequences within the 18S rRNA sequence (14). The main peak of association was located around position +1103 relative to A 1 , in the 3′ part of the central domain.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…This sequence is not known to be the target of any endoribonuclease activity. However, recent RNA–protein crosslinking data (CRAC analysis (39)) showed that the Utp24 endoribonuclease was predominately associated with sequences within the 18S rRNA sequence (14). The main peak of association was located around position +1103 relative to A 1 , in the 3′ part of the central domain.…”
Section: Resultsmentioning
confidence: 99%
“…For this purpose, we constructed a strain lacking the RRP6 gene, strongly accumulating 23S, in which HA-tagged Utp24 is expressed under the control of the tetracycline repressible promoter (pTetO7). This strain was next transformed with a plasmid expressing either WT, Utp24 PIN mutant allele (Utp24-D68N) (13,14) or no protein. Ten hours following addition of doxycycline, fully functional genomic Utp24 is largely depleted (Supplementary Figure S2) and the only available source of Utp24 in the cell is the version expressed from the plasmid (WT, PIN mutant or mock).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations